A portable point-of-care testing device for forward blood typing with hemophilia diagnosis. - Chang, Yaw-Jen; Yeh, Shang-Fen; Chen, Pin-Jyun (Biomedical Microdevices, 2023)
This paper presents a portable point-of-care testing (POCT) device to conduct simultaneous and on-site tests of ABO and Rh(D) forward blood typing and hemophilia diagnosis using only a small amount of human whole blood sample. The POCT device consisted of a spinning module, a measuring circuit, an interdigitated electrode (IDE) for hemophilia diagnosis, and three disposable microfluidic chips for bioassays with anti-A, anti-B, and anti-D, respectively, and measurement of the concentration of factor VIII. Agglutination will occur if red blood cells (RBCs) are exposed to the corresponding antibody. To evaluate the degree of RBC agglutination, a linear sweep voltage, ranging from − 0.5 to + 0.5 V, was applied to the electrodes of the microfluidic chip and the resulting current was measured. For different levels of agglutination, the measured I–V curves were explicitly discriminated, providing five clinical levels from non-agglutination (level 0) to strong agglutination (level 4). The quantitative norm obtained from cubic fitting function of each I–V curve served as the criterion to represent this agglutination level. The ABO blood type was determined by both agglutination levels of the blood sample reacting with anti-A and anti-B. The degree of agglutination with anti-D gave the Rh(D) type. Moreover, the concentration of factor VIII was detected for the determination of hemophilia. Without requiring expensive equipment, this POCT device is especially suitable for usage in emergency or natural disasters to provide quantitative testing in rescue and relief operations.